ANALISIS PENGARUH VALUE BASED ADOPTION MODEL TERHADAP NIAT KONSUMEN UNTUK MENGGUNAKAN WEARABLE TECHNOLOGY - SMART WATCH DI INDONESIA PADA MASA PANDEMI COVID-19 - Lydia Ari Widyarini (Universitas Lambung Mangkurat, 2021)
Wearables technology as a smart complement tobe one of essensial delivery information, function of daily use and healthcare, specially during the COVID 19 pandemic are presented. People have to control their health and do the activities to rise body imunity. Wearables systems significantly reduce the risk of infectious disease transmission. This study aims to comprehensively examine the adoption of wearable technology. A new model VAM (Value-based Adoption Model) combining value and TAM (Technical Acceptance Model) was developed and analyse with a set of variables benefit and sacrefice. Variables benefit consist of usefulness and enjoyment: variables sacrefice consist of technically fee and perceived fee for the wearable technology devices. Using questionaire and using Structural Equation Model analys 262 respondents age between 17-60 years old, many kinds of profesion and knows about wearable technology and using internet. The result shows that Perceived value was affected by perceived usefulness, perceived enjoyment and Technically, but it’s not significance affacted by perceived fee. This study holds considerable significance as it proposes a new approach to IoT (Internet of Things)-based wearable technology adoption using VAM and TAM. Through these model, the study determined that it is imperative for businesses to constitute and secure appropriate the product for people to use IoT-based wearable technology to reduce Covid 19 risk.